Experimental comparison of thermal performance in PV–AC and PV–DC solar cooker systems under tropical conditions - Siwan Edi Amanta Perangin Angin; Yogie Probo Sibagariang; Richard A.M Napitupulu; Jonner Manihuruk (Jurnal Polimesin, 2026)
Photovoltaic-based electric cooking systems are receiving attention as one of clean cooking development in tropical regions. However, experimental comparisons between PV–AC and PV–DC solar cooker systems under identical operating conditions and practical household water loads remain limited. This study experimentally compares the thermal performance of PV–AC and PV–DC solar cooker systems under outdoor tropical conditions in Medan, Indonesia, using identical vessels and water loads of 1.0, 1.5, and 2.0 kg. The analysis focuses on water temperature evolution, heating rate, and time-to-boil (t₁₀₀) under varying electrical and environmental conditions. The results show that the PV–AC system maintained a more stable electrical input of approximately 145–186 W, producing cooking power of 190–210 W and thermal efficiency of 80–90%. In comparison, the PV–DC system operated at 115–160 W with thermal efficiency of 55–70%. For a 2.0 kg water load, the PV–AC system achieved water temperatures of approximately 95–100 °C, whereas the PV–DC system reached about 80–90 °C under similar solar irradiance conditions. The results indicate that electrical power stability significantly affects thermal performance, and that the PV–AC system provides more consistent water heating under tropical operating conditions.